2021
DOI: 10.3310/pgfar09020
|View full text |Cite
|
Sign up to set email alerts
|

A complex intervention to reduce avoidable hospital admissions in nursing homes: a research programme including the BHiRCH-NH pilot cluster RCT

Abstract: Background An unplanned hospital admission of a nursing home resident distresses the person, their family and nursing home staff, and is costly to the NHS. Improving health care in care homes, including early detection of residents’ health changes, may reduce hospital admissions. Previously, we identified four conditions associated with avoidable hospital admissions. We noted promising ‘within-home’ complex interventions including care pathways, knowledge and skills enhancement, and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 112 publications
(107 reference statements)
3
10
0
Order By: Relevance
“…This proved to be too complex to manage and could not be implemented successfully during the entirety of the INTERCARE study. This is similar to findings from the pilot BIRCH program where the STOP&WATCH tool was seldom used despite initial enthusiasm [47]. NHs achieved high implementation fidelity for ISBAR and sustained it after the intervention ended.…”
Section: Isbar and Stopandwatch Toolssupporting
confidence: 79%
“…This proved to be too complex to manage and could not be implemented successfully during the entirety of the INTERCARE study. This is similar to findings from the pilot BIRCH program where the STOP&WATCH tool was seldom used despite initial enthusiasm [47]. NHs achieved high implementation fidelity for ISBAR and sustained it after the intervention ended.…”
Section: Isbar and Stopandwatch Toolssupporting
confidence: 79%
“…It has also been described in the literature that education delivered to nursing homes can effect change on an individual level that does not translate to changes on an organisation level [ 21 ], which may have been a factor in ECHO. Similar studies that sought to reduce the number of nursing home residents being transferred to the emergency department also did not succeed in their primary outcome [ 7 9 ]. It is possible that the outcomes of such interventions/education programmes are best measured in other patient/staff/institution markers, such as advance care planning or arbitrary assessment of learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there has been much study on interventions aiming to reduce emergency transfer of nursing home residents to hospital [ 7 9 ]. A common theme among these studies is the development of a new process, tool or care pathway which is then implemented within the nursing home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some RCTs focusing on clinical outcomes of NHRs showed indifferent findings [ 19 , 20 ]. A recent English pilot RCT found no significant effect on avoidable hospitalisations by implementing a complex intervention [ 21 ]. However, a systematic review on interventions in NHs revealed benefits on NHRs’ health, if GPs were involved [ 22 ].…”
Section: Introductionmentioning
confidence: 99%